Local Gastronomic Analysis as an Effort to Positioning Madura Tourist Destinations (Songkem Duck Culinary Case Study) - Rahmawati, Farida Nurul; Suryandari, Nikmah; Adhidharma, Ferry; Rakhmawati, Yuliana (Jurnal Komunikasi, 2024)
Local gastronomy is one of the tourist attractions that can be a positioning strategy for a tourist destination. This study aims to (1) identify the values and social philosophy of Madurese people in songkem duck cuisine; (2) explore the form of realization of the value of Madurese social philosophy in songkem duck dishes; (3) analyze the potential of local gastronomy as an indicator of the positioning of tourist destinations in Madura. This research is qualitative research with case study method. The informant selection technique is carried out using snowball sampling, which is a technique of taking informants with a small initial number and gradually becoming as many as needed. The data analysis technique used is a triangulation technique by double-checking with informants. The results showed that based on its history, duck songkem is a Madurese food served as a form of respect for kyai as a central figure in the Madura social system. The local values embodied in songkem duck cuisine are reflected in local gastronomic attractions, including raw materials, processing, distinctive culinary flavors, food presentation and are demonstrated by ethics, courtesy and friendly service to guests. Songkem duck dish has authentic, iconic, unique and distinctive characteristics with the locality of the local community being a competitive advantage to become the positioning of Madura tourist destinations. This culinary quality needs to be improved through gastronomic tourism attractions with the support of the government and all stakeholders.